Phytochemical screening of belalai gajah (clinacanthus nutans) and its antibacterial activity / Nur Musfirah Suhaimi - Suhaimi, Nur Musfirah (2017)
This study point out the phytochemical analysis and the antibacterial activity of a medicinal plant, Clinacanthus nutans (C. nutans). The sample were extracted using cold extraction method with different polarity of solvent such as hexane, ethyl acetate and methanol. Phytochemical analysis was determined through foam test, ferric chloride test, lead acetate test and alkaloids test. Antibacterial activity was analyze by disc diffusion method using Salmonella typhi (S. typhi), Staphylococcus aureus (S. aureus), Escherichia coli (E. coli), and Bacillus subtilis (B. subtilis). Phytochemical analysis for the hexane extract show the positive result for alkaloid and saponins. While the methanol extract indicates the present of flavonoid and saponins. However, the ethyl acetate extract show no significant phytochemical constituents. Apart from that, antibacterial activity show methanol crude extract give a highest inhibition against S. aureus. This show that C. nutans has a possible benefit to be antibacterial agent.